2012
DOI: 10.1590/s0073-47212012000400005
|View full text |Cite
|
Sign up to set email alerts
|

The diet of the South American sea lion (Otaria flavescens) at Río Negro, Patagonia, Argentina, during the winter-spring period

Abstract: ABSTRACT. The South American sea lion, Otaria flavescens (Shaw, 1800) population is steadily expanding along the Patagonian coast of Argentina in the last decades. However, little is known about the feeding ecology of the species in the area. The aim of this study was to analyze the food habits of O. flavescens from 91 scats collected at Río Negro province, during the winter and spring of 2005. Fish occurred in 96% of scats containing prey remains, followed by cephalopods (26%). Raneya brasiliensis (Kaup, 1856… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
(21 reference statements)
6
21
0
3
Order By: Relevance
“…Nevertheless, the use of the same resource at different times or spatial locations and of different age classes does not necessarily imply that the interaction between sea lions and fisheries is less strong (Szteren et al 2004). Still, considering that the main prey item (R. brasiliensis) of O. flavescens is not targeted by commercial fisheries and that it only represents a small percentage of the discards, the overlap in the use of resources by the former and the latter may not be substantial, at least during the summer season.On the other hand, the present results show that Octopus tehuelchus was the most important cephalopod prey of South American sea lions in summer, which coincides with previous results reported by Bustos et al (2012) for the spring of 2005. This octopod species is an important coastal resource for artisanal fishing in the San Matías Gulf, with this activity taking place during the spring and summer seasons (Storero et al 2010).…”
supporting
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, the use of the same resource at different times or spatial locations and of different age classes does not necessarily imply that the interaction between sea lions and fisheries is less strong (Szteren et al 2004). Still, considering that the main prey item (R. brasiliensis) of O. flavescens is not targeted by commercial fisheries and that it only represents a small percentage of the discards, the overlap in the use of resources by the former and the latter may not be substantial, at least during the summer season.On the other hand, the present results show that Octopus tehuelchus was the most important cephalopod prey of South American sea lions in summer, which coincides with previous results reported by Bustos et al (2012) for the spring of 2005. This octopod species is an important coastal resource for artisanal fishing in the San Matías Gulf, with this activity taking place during the spring and summer seasons (Storero et al 2010).…”
supporting
confidence: 93%
“…2). This is in line with previous dietary studies that also reported fish to be the dominant prey items consumed by this otariid (Thompson et al 1998, Koen Alonso et al 2000, Suárez et al 2005, Romero et al 2011, Bustos et al 2012.In the present study, Raneya brasiliensis was clearly the dominant prey species throughout the sampling period, since it was the most frequent and abundant fish item and contributed 75% to the IRI (Table 1) On the other hand, some authors have suggested that hake Merluccius hubbsi make an important contribution to the diet of the South American sea lions from Patagonia, after analysis of the stomach contents of individuals found dead on the beach or recovered from incidental catches (Koen Alonso et al , Romero et al 2011). However, in other studies based on scat analysis, including the present one, hake was shown to be absent or poorly represented in the diet of Otaria flavescens (Table 2) (Suárez et al 2005, Bustos et al 2012).…”
supporting
confidence: 91%
See 3 more Smart Citations